Readiness to Seek Social Worker’s Intervention Directed to Marriage Stability (on the example of urban citizen's of Khuzestan province of Iran) - Khachatryan, Artak; Molayi, Nasrin (Journal of Sociology: Bulletin of Yerevan University, 2018)
The traditional family structure and functions in the Iranian society are experiencing a range of changes with regard to the issues of whether or not the former household size should be maintained or the minimum marriageable age should be raised, which results in active involvement of modern women in public societal life, her gaining of some freedom when choosing a partner, and increasing the number of working women. Even the entire powerful system of cultural and legal restrictions in Iran is unable to slow down the increasing number of divorces of married couples as a result of these changes. Consequently, the professional intervention of social worker to provide some solution to marital conflicts and marital problems is becoming more and more robust. The sociological study of couples in Khuzestan Province has revealed the degree of perception of marital conflicts as a threat to marriage stability and the possibility to discuss these issues outside of the family, and the degree of willingness of married couples with different demographic parameters to seek the intervention of a social worker. The degree of readiness in couples to seek the help of a social worker is primarily justified by incurred financial costs, as well as the public opinion and trust in a specialist.
Keywords: married couple, marriage stability, marital conflicts, social work, professional intervention